Schottky diodes based on the zinc selenide semiconductor crystals - Voronkin, E. (Functional Materials, 2013)
The problems of raw materials obtaining for UV detectors such as crystalline elements based on zinc selenide(ZnSe) have been discussed. Electrical parameters of these elements have been determined. Method of Schottky diodes based on ZnSe manufacturing with various metal contacts (Ni, Pt, Pd, Al) has been presented. From the current-voltage characteristics of these diodes their main characteristics have been identified: range of work, dark currents and range of light sensitivity. The comparative characteristics of the diodes have been shown. It was defined that sensitivity of the diodes with platinum contacts under ultraviolet radiation exposure in 2–3 times higher than of the diodes that have contacts from nickel and palladium. The spectral characteristics confirm the efficiency of using the Schottky diodes on the base of A₂B₆ semiconductors, particularly ZnSe, for detection of ultraviolet radiation.